Strategies of Maintaining Immigrant Language in a Mega Cosmopolis: The Case of Idoma in Lagos State, Nigeria - Nwagbo, Osita Gerald (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
As a result of the presence of numerically dominant languages in mega cities in Nigeria, such as Lagos, maintenance of minority home languages is a huge challenge. Several studies have been carried out on maintenance of native languages in urban centers, but none has been undertaken on Idoma in Lagos, Nigeria. Consequently, this study examines the state of Idoma language in Lagos where the Idoma are a minority group with a view to estimating the strategies adopted by Idoma to maintain their language. This is with a view to evaluating home-based strategies, culture-based strategies, community-based strategies, network-based strategies and entertainment-based strategies. Through snowball samplig, a total of 200 families were selected for the study, and the questionnaire was used to elicit information from respondents, in addition to interviews. The result shows that few participants utilized home-based, culture-based strategies and entertainment-based strategies, while more participants adopted community-based and network-based strategies. Generally, it was found that the Idoma participants in the study were not taking proactive steps towards maintaining their heritage language, even when it was evident that their children had already shifted to English and Yoruba, the host community language. The result provides the need for holistic and sustained effort towards preserving Idoma, especially in multilingual spaces such as Lagos where its existence is precarious. Keywords: Idoma, Heritage language, Heritage language maintenance, Yoruba, Lagos State,